2012
DOI: 10.1016/j.jcmg.2011.11.020
|View full text |Cite
|
Sign up to set email alerts
|

RV Dysfunction In Pulmonary Hypertension Is Independently Related To Pulmonary Artery Stiffness

Abstract: PA stiffness is independently associated with the degree of RV dysfunction, dilation, and hypertrophy in PH. RV adaptation to chronic pressure overload is related not only to the levels of vascular resistance (steady afterload), but also to PA stiffness (pulsatile load).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
136
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(152 citation statements)
references
References 38 publications
11
136
0
5
Order By: Relevance
“…The linearity of the RVEF-R relationship for RVEF >35% is consistent with the linear relationship observed in mild and moderate PAH. 11 Similar to the linear-R model, the mixed linear model is consistent with the curvilinear RVEF-C relationship observed by Stevens et al 18 In Table 1, we summarize strengths and weaknesses of the three models on the basis of clinical evidence. In Figure 2, we directly compare the results from our models with the empirical correlations derived from the limited clinical data available.…”
Section: Methodssupporting
confidence: 74%
See 1 more Smart Citation
“…The linearity of the RVEF-R relationship for RVEF >35% is consistent with the linear relationship observed in mild and moderate PAH. 11 Similar to the linear-R model, the mixed linear model is consistent with the curvilinear RVEF-C relationship observed by Stevens et al 18 In Table 1, we summarize strengths and weaknesses of the three models on the basis of clinical evidence. In Figure 2, we directly compare the results from our models with the empirical correlations derived from the limited clinical data available.…”
Section: Methodssupporting
confidence: 74%
“…As a result, RVEF is clearly more sensitive to changes in C in severe PAH than mild or no PAH, which is supported by clinical evidence. 18 For our second model, we alternatively hypothesize that RV function is equally sensitive to changes in C at any stage of PAH, resulting in a linear relationship between RVEF and C (linear-C model; Fig. 1c, 1d ).…”
Section: Methodsmentioning
confidence: 99%
“…As Boerrigter et al 24 reported in patients with pulmonary arterial hypertension, progressive enlargement in the pulmonary arterial diameter measured by using cardiac MRI occurs independent of changes in hemodynamics. A possible explanation for this phenomenon is that underlying pulmonary vascular disease decreases pulmonary arterial wall distensibility during stability, 25,26 but the reduced vascular distensibility is overcome during AECOPD by factors such as dynamic hyperinflation, altered gas exchange, hypoxic vasoconstriction, increased circulating volume (pulmonary edema or diastolic dysfunction), increased cardiac output, and inflammation. [27][28][29] Following exacerbations, the vessel returns to its normal size due to its impaired distensibility.…”
Section: Discussionmentioning
confidence: 99%
“…Indices of proximal PA distensibility or stiffness quantified by echocardiography,13, 14 computed tomography angiography,15 and magnetic resonance imaging12, 16, 17, 18, 19 are attractive noninvasive indices of PH in humans. These indices correlate with “gold standard” invasive measurements of pulmonary vascular resistance and PA pressure,14, 15, 18 are reliable and early noninvasive indicators of PH (even when only exercised‐induced PH is present),16, 18 predict mortality,12, 17, 18 and help predict acute drug responsiveness 19. Recently, a right pulmonary artery distensibility (RPAD) index quantified by echocardiography, essentially a shortening fraction of the right PA, was evaluated in dogs affected with heartworm disease and various degrees of PH 6.…”
mentioning
confidence: 99%